Clinical study of XiangShaLiuJunZi decoction combined with S-1 as maintenance therapy for stage III or IV gastric carcinoma and colorectal carcinoma - Hong, Xiao-Cui (Medicine (Baltimore), 2020)
INTRODUCTION: S-1, a new oral fluorouracil chemotherapeutical drug, has been increasingly used in clinical maintenance after first-line chemotherapy for stage III or IV gastric carcinoma (GC) and colorectal carcinoma (CRC) for its own advantages. XiangshaLiujunzi Decoction (XSLJZD), a classic traditional Chinese medicine (TCM) formula with effects of alleviating the adverse reactions of chemotherapy and improving the quality of life of cancer patients has been gradually confirmed, with no more reports about the maintenance therapy mode of combination of chemotherapeutic drugs and TCM. We designed the study of XSLJZD combined with S-1 in the maintenance therapy of Stage III or IV GC and CRC, and hoped that this research program will go further and comprehensively evaluate its efficacy and safety. OBJECTIVES: The aim of this study was to determine the efficacy and safety of XSLJZD combined with S-1 in the maintenance therapy of stage III or IV GC and CRC. METHODS: This study is an open, single-center, randomized study. Patients with stage III or stage IV GC and CRC will be randomized (1:1) into S-1group, S-1 combined with XSLJZD group for 5 years of maintenance therapy. The primary endpoint was progression-free survival, and secondary end point was overall survival and Quality of Life Assessment (QOLA), which include an improvement in symptoms before and after treatment, Karnofsky Performance Status, and adverse events assessment. DISCUSSION: This study will provide meaningful clinical information about the combination of chemotherapeutic drugs S-1 with TCM in the maintenance therapy of stage III or IV GC and CRC. TRIAL REGISTRATION: Chinese Clinical Trial Registry: ChiCTR-INR-16008575.